Frontal lobe activation in older adults and youngs: an electroencephalographic analysis during exergame for postural balance (Research, Society and Development, 2020)
Objective: to investigate the frontal lobe cortical activation of older adults and youngs during an exergame session for postural balance. Methodology: cross-sectional study with 20 individuals (10 older adults and 10 youngs) attended exergaming session. Initially, sociodemographic and clinical assessments were carried out and then, an electroencephalographic (EEG) assessment with Emotiv EPOC® during the execution of Nintendo Wii Fit Penguin slide exergame was done. Eight channels of the frontal region and alfa and beta waves were used for analysis. The EEG data was recorded by Emotiv TestBench and imported into MatLab®. SPSS program, Mann-Whitney test and significance level of p